Sosialisasi Identifikasi Manajemen Risiko dalam Penyelenggaraan Rekam Medis Elektronik di UPT Puskesmas Pulo Brayan - Sitorus, Mei Sryendang; Simanjuntak, Marta; Daeli, Cosmas Samuel; Hutasoit, Theresia; Erlindai, Erlindai; Sihite, Geovani Arta (Universitas Pahlawan Tuanku Tambusai, 2025)
Electronic Medical Records are medical records created using an electronic system intended for organizing Medical Records (Permenkes RI, 2022. Health centers are required to have and organize medical records for every patient who receives services (Permenkes RI, 2008). Integrated risk management is the process of identifying, analyzing, evaluating and managing all potential risks and is applied to all units or activities starting from the preparation of strategic plans, program and budget implementation, accountability and monitoring evaluation and reporting (Permenkes RI, 2019). In the Pulo Brayan Health Center Medical Records Unit, factors that influence risk were found, namely: physical, biological, psychological, chemical, and ergonomic factors. Activities were carried out by socializing the Management of Risk Management and SOP for Risk Management in the Medical Records Unit and revisions. Continued with risk identification and assessment. The results of the physical factors showed that medical record officers had the potential to experience eye fatigue due to exposure to computer radiation which can be overcome by using anti-radiation to reduce the risk. Psychological factors include increased emotions due to network disruptions, overcome by increasing network capacity and maintenance. Ergonomic factors Muscle tension is overcome by using a more ergonomic work chair.